Functional genomic analysis of the 68-1 RhCMV-Mycobacteria tuberculosis vaccine reveals an IL-15 response signature that is conserved with vector attenuation - Sung, Cheng-Jung; Whitmore, Leanne S.; Smith, Elise; Chang, Jean; Tisoncik-Go, Jennifer; Barber-Axthelm, Aaron; Selseth, Andrea; Feltham, Shana; Ojha, Sohita; Hansen, Scott G.; Picker, Louis J.; Gale, Michael (Frontiers in Immunology, 2024)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb) is a deadly infectious disease having a major impact on global health. Using the CMV vector for development of novel vaccines is a promising new strategy that elicits strong and durable, high frequency memory T cell responses against heterologous immunogens. We conducted functional transcriptomic analysis of whole blood samples collected from cohorts of rhesus (Rh) macaques that were administered RhCMV/TB vector using a prime-boost strategy. Two modified CMV vectors were used in this study, including 68-1 RhCMV/TB-6Ag (encoding 6 Mtb protein immunogens, including Ag85A, ESAT-6, Rv3407, Rv2626, Rpf A, and Rpf D) and its attenuated variant, 68-1 RhCMV/Δpp71-TB-6Ag (a cell-to-cell spread-deficient vaccine vector lacking the Rh110 gene encoding the pp71 tegument protein). Bulk mRNA sequencing, differential gene expression, and functional enrichment analyses showed that these RhCMV/TB vaccines induce the innate and adaptive immune responses with specific transcriptomic signatures, including the IL-15-induced protective gene signature previously defined to be linked with protection against simian immunodeficiency virus (SIV) by the 68-1 RhCMV/SIV vaccine. While both vectors exhibited a transcriptomic response of the IL-15 protective signature in whole blood, we show that lack of pp71 does not maintain induction of the protective signature for the full duration of the study compared to the parental non-attenuated vector. Our observations indicate that RhCMV vector vaccines induce a transcriptomic response in whole blood that include a conserved IL-15 signature of which vector-encoded pp71 is an important component of response durability that upon future Mtb challenge may define specific vaccine protection outcomes against MTb infection.